Multidimensional characterization of the Innovation Stimulus Program in Mexico - Flores Payan, Lucio; Tello Medina, Jorge Benjamín (Journal of the University of Zulia, 2021)
This paper develops an analysis that enables the identification of some of the results achieved by the Science, Technology and Innovation Policy (CTI) in Mexico, visualized in the effects of the implementation of the Innovation Stimulus Program (ISP). The analysis was carried out in order to quantify the results of the PEI. Two multidimensional indices were designed and calculated, the first based on fuzzy logic theory, the other as a synthetic index. The results show the need to propose new mechanisms in normative and institutional matters to achieve firm agreements and associations between the public and private sectors on issues related to risk capital, fiscal incentives or others, that allow to carry out clear and common objectives, so that the contribution of the CTI is for the economic development of the entire country. Likewise, the goodness of the use of fuzzy sets in the construction of multidimensional indexes is manifested in a way that allows greater precision because its construction is based on the creation of a continuous universe of data, at the same time that it makes possible the handling of a greater number of variables.